Case report: Kimura's disease with minimal degenerative glomerulopathy without eosinophil infiltration responds to mycophenolate mofetil treatment - Han, Qing; Han, Jie; Wang, Weitao; Gao, Jie; Qiao, Youzhen; Jia, Junfeng; Zhang, Kui; Zheng, Zhaohui; Zhu, Ping (Frontiers in Medicine, 2023)
Kimura's disease (KD) is a rare chronic progressive immune inflammatory disease. The etiology is unknown and manifests as a chronic inflammatory process, which is more common in young Asian men. The clinical manifestations are painless subcutaneous swelling of the head and neck and periauricular lymphadenopathy, which is slow growing and has a benign course.KD may involve the kidney, and pathological examination revealed eosinophil infiltration in the renal tissue. Proteinuria has been reported in 12% to 16% of KD cases, and about 60% to 70% of KD patients will develop nephrotic proteinuria. KD is easily confused with nephrotic syndrome, because KD does not have specific clinical manifestations, laboratory and imaging, and early misdiagnosis is easy. We report a case of KD that was biopsy-proven to have minimal lesion glomerulopathy after approximately 11 years. In this report, we describe a clinical case of KD with nephrotic syndrome, but there's no eosinophil infiltration in the kidneys. The clinical manifestations of KD recurrence were bilateral eyelid edema, bilateral lower limb swelling, and massive proteinuria in response to mycophenolate mofetil treatment (1.5g).